Anomalies of tooth formation in hypohidrotic ectodermal dysplasia - MICHALA O. LEXNER, ALLAN BARDOW, JENS MICHAEL HERTZ, LIS A. NIELSEN, & SVEN KREIBORG (IAPD and Blackwell, 2007)
The X-linked hypohidrotic ectodermal dysplasia (HED) is the most common type of ectodermal dysplasia. The clinical identification of possible heterozygous females can be difficult because of the varying degrees of clinical signs caused by Xchromosome inactivation.